Алельні варіанти генів поліфенолоксидази PPO-A1 та PPO-D1 у сортів озимої пшениці української селекції - Степаненко, А.І.; Моргун, Б.В.; Трояновська, А.В.; Рибалка, О.І.; Великожон, Л.Г. (Фактори експериментальної еволюції організмів, 2014)
Aims. Polyphenol oxidase (P.O), a ubiquitous enzyme in plants, is associated with browning and discoloration of breeding products such as pan bread, steamed bread, pasta, foodstuff of freezing dough. There are five genes that control the P.O activity: P.O-A1, P.O-D1, P.O-A2, P.O-B2 and P.O-D2. Genes P.O-A1, P.O-D1 can occur in several allelic variants: alleles of high activity (P.O-A1a and P.O-D1b), alleles of low activity (P.O-A1b and P.O-D1a) which encode different types of P.O enzymes. Methods. The most reliable way to assess the allelic state of P.O gene is molecular identification STS markers P.O33 and P.O29. Results. Among the studied wheat by codominant and dominant molecular markers two varieties (Bilyava and Ednist) carrying low activity P.O-A1, P.O-D1 alleles and 26 varieties containing one low activity allele P.O-D1a were identified. Conclusions. The results of the study can be used efficiently to identify genotypes with low P.O activity in wheat breeding.